Zhmud. L. (2012). Pythagoras and the Early Pythagoreans. Oxford, Oxford University Press - McKirahan, Richard (Revista Archai, 2014)
Zhmud. L. (2012). Pythagoras and the Early Pythagoreans. Oxford, Oxford University Press